Integrating the effects of price fairness and Islamic altruism with the TPB model The case of Islamic mortgage adoption - Khadijah M. Sayuti; Hanudin Amin (Emerald Publishing Limited, 2020)
Purpose – The purpose of this study is to examine the impacts of price fairness and Islamic altruism on the Islamic mortgage adoption along with theory of planned behaviour’s (TPB’s) constructs (i.e. attitude, subjective norm and perceived behavioural control). Attitude is also analysed as a mediator in this study. Design/methodology/approach – Using TPB as a baseline theory, this study analyses the Islamic mortgage adoption involving a total of 281 Muslim consumers in Malaysia using partial least squares. Findings – The results indicate that attitude, subjective norm, perceived behavioural control and price fairness significantly influence Muslim bank customers’ intention to choose Islamic home financing products. Other interesting findings are also provided. Research limitations/implications – This study contains three limitations that include the geographical constraint, respondents’ selection and the limited number of factors used. Practical implications – The results obtained can serve as a guideline for bank managers or marketers to generate better strategies, which are dynamic to improve the acceptance rate of Islamic mortgage. Originality/value – This study extends the TPB flexibility to integrate with price fairness and Islamic altruism in the Islamic mortgage adoption context.